2006
DOI: 10.1186/1472-6920-6-48
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction and resilience in medical school – a six-year longitudinal, nationwide and comparative study

Abstract: BackgroundThis study examined the relationship between life satisfaction among medical students and a basic model of personality, stress and coping. Previous studies have shown relatively high levels of distress, such as symptoms of depression and suicidal thoughts in medical undergraduates. However despite the increased focus on positive psychological health and well-being during the past decades, only a few studies have focused on life satisfaction and coping in medical students. This is the first longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
184
3
22

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(225 citation statements)
references
References 41 publications
16
184
3
22
Order By: Relevance
“…As other authors do not report domain-specific results (Kjeldstadli et al 2006;Tyssen et al 2009), we cannot compare our findings to other studies.…”
Section: Life Satisfaction In Young Physicians Compared With An Age-mcontrasting
confidence: 54%
See 3 more Smart Citations
“…As other authors do not report domain-specific results (Kjeldstadli et al 2006;Tyssen et al 2009), we cannot compare our findings to other studies.…”
Section: Life Satisfaction In Young Physicians Compared With An Age-mcontrasting
confidence: 54%
“…Restrictively, this sample includes doctors of all ages. In a Norwegian prospective study (Kjeldstadli et al 2006) a decrease of life satisfaction during medical school is reported. Both samples cannot be compared with our study sample.…”
Section: Life Satisfaction In Young Physicians Compared With An Age-mmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Depression affect students both professionally and personally, which result in diminished life satisfaction among students. 6 A literature review identified only a few studies conducted in Pakistan on depression among medical students. 4,7,8,9,10,11 As there is a lack of data regarding prevalence of depression and the role of precipitating factors of depression among medical students in Pakistan so, the present study was undertaken to look for prevalence of depression among medical students of Sargodha Medical College, Sargodha, Punjab Pakistan, using a diagnostic tool i.e., Patient Health Questionnaire (PHQ-9) 12 for depression, associations of depression with demographic and educational characteristics and the extent to which stressors predict depression.…”
Section: Introductionmentioning
confidence: 99%